Synthesis, photophysics and photochemistry studies on non-peripherally tetra-substituted Zn(II) and In(III) phthalocyanines bearing ferulic acid units - Gorduk, Semih (ELSEVIER, 2019)
In this study, we reported synthesis, characterization, photophysical, photochemical and aggregation properties of new non-peripherally tetra-substituted Zn(II) (FA-ZnPc) and In(III) (FA-InPc) phthalocyanine photosensitizers bearing ferulic acid units. The synthesized compounds were characterized by Elemental analysis, FT-IR, UV-vis, NMR and MS techniques. Aggregation behaviors of these phthalocy-anines were studied in various solvents such as DMSO, DMF, and THF and no aggregation was detected in the mentioned solvents for both phthalocyanines. In addition, photophysical (Fluorescence quantum yield) and photochemical properties (Singlet oxygen quantum yield and photodegradation quantum yield) of the synthesized phthalocyanines were examined in these solvents. The results showed that FA-ZnPc has the highest singlet oxygen yield in DMSO. Further, the photochemical studies showed that both FA-ZnPc and FA-InPc owing to their high singlet oxygen quantum yields in different solvents (range from 0.65 to 0.96) can be used as photosensitizers in photodynamic therapy (PDT). (C) 2019 Elsevier B.V. All rights reserved.
Keywords: Ferulic acid; Phthalocyanine; Photochemical; Photophysical; Singlet oxygen; ZINC PHTHALOCYANINE; IN-VITRO; QUANTUM YIELDS; METAL-FREE; COMPLEXES; PHOTOSENSITIZERS; ABSORPTION; SOLVENT; DERIVATIVES; GALLIUM; Chemistry